Let us be Muslims - Maudoodi, Syed Abul ʻAla 1903-1979 (The Islamic Foundation, 1991)
This translation of Khutabat covers themes such as Iman, Islam, the prayer, fasting, almsgiving, pilgramage and Jihad.